2010
DOI: 10.1007/s00440-010-0266-y
|View full text |Cite
|
Sign up to set email alerts
|

Lyapunov exponents of Green’s functions for random potentials tending to zero

Abstract: We consider quenched and annealed Lyapunov exponents for the Green's function of − + γ V , where the potentials V (x), x ∈ Z d , are i.i.d. nonnegative random variables and γ > 0 is a scalar. We present a probabilistic proof that both Lyapunov exponents scale like c √ γ as γ tends to 0. Here the constant c is the same for the quenched as for the annealed exponent and is computed explicitly. This improves results obtained previously by Wang. We also consider other ways to send the potential to zero than multipl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
4
17
0
Order By: Relevance
“…It was shown in [KMZ12] that if E[V ] < +∞ (we use E[V ] as shorthand for E[V (0)]), then as λ tends to 0,…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in [KMZ12] that if E[V ] < +∞ (we use E[V ] as shorthand for E[V (0)]), then as λ tends to 0,…”
Section: Introductionmentioning
confidence: 99%
“…Recently, [Wa01a,Wa02,KMZ12] studied this question under the additional assumption that E[V ] is finite (where we write E[V ] as shorthand for E[V (0)]). They found that, as β tends to 0,…”
Section: Introductionmentioning
confidence: 99%
“…Discussion and an open problem. There are many papers concerning the relationship of the quenched and annealed Lyapunov exponents of a random walk in a random potential on Z d , d ≥ 1 (see [Fl08], [Zy09], [KMZ11], [IV12c], [Zy12], and references therein). Lyapunov exponents represent the exponential decay rates of the quenched and annealed survival probabilities, P ω (τ y < ∞) and E(P ω (τ y < ∞)) respectively.…”
Section: 2mentioning
confidence: 99%